The Association Between Demographic Factors and Quality of Life in Indonesian Older Adults with Hypertension Attending Outpatient Unit - Rosida; Nga Thi Thuy Nguyen; Anung Ahadi Pradana (STIKES Hesti Wira Sriwijaya, 2025)
Introduction: Aging process often results in functional declines in various bodily systems, one of which is the cardiovascular system. Hypertension is a major risk factor for cardiovascular diseases, characterized by an increase in systolic blood pressure > 140 mmHg and diastolic blood pressure > 90 mmHg. This aging process affects older adults and subsequently requires efforts to improve their quality of life in order to achieve well-being. Quality of life refers to an individual's perception of their position in life in relation to cultural and societal norms, values, goals, desires, standards, and interests. This study aims to examine which demographic variables are associated with the quality of life among older adults with hypertension in the outpatient unit of a private hospital. Method: The research employed a non-probability sampling method, specifically total sampling, with 32 respondents, using a cross-sectional approach based on pre-established inclusion and exclusion criteria. Results: The results indicated that demographic variables such as age (p-value 0.066), gender (p-value 0.593), employment status (p-value 1.000), education (p-value 0.057), marital status (p-value 0.295), income (p-value 1.000), and residence (p-value 0.238) were not significantly associated with the quality of life of older adults with hypertension. Conclusion: In conclusion, there were no significant associations between age, gender, employment status, education, marital status, income, and residence with the quality of life of older adults with hypertension in the outpatient unit.